Bezdrátový datalogger pro monitorování prostředí uchovávaných léčiv – klientská část - Štopl, Vlastimil (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2024)
Cílem této práce je navrhnout zařízení klient-server pro automatické zaznamenávání teploty prostředí pro uložení léčiv. Tato práce je zaměřená na klientskou část. V teoretické části je uvedena příslušná legislativa k uložení léčiv a definice Internetu věcí. Praktická část obsahuje samotný systémový návrh zařízení a jeho realizaci. Jako řídící jednotka byl zvolen mikrokontrolér ESP8266 ve spojení se senzorem DS18B20.

The aim of this work is to design a client-server device for automatic recording of environmental temperature for the storage of pharmaceuticals. This work focuses on the client part. The theoretical section includes relevant legislation for pharmaceutical storage and definitions of the Internet of Things. The practical part comprises the actual system design of the device and its implementation. The chosen control unit is the ESP8266 microcontroller in conjunction with the DS18B20 sensor.
Wireless data logger for environmental monitoring - client-side
Keywords: ESP8266; senzor teploty; legislativa; Internet věcí; UDP; NTP; ESP8266; temperature sensor; legislation; Internet of Things; UDP; NTP